Astrotheology as a prophetic wormhole that relates spacetime to eschatological transformation - A.C. Pieterse (Acta Theologica)
One of the peculiarities that comes to the fore in reflecting on Scripture and the behaviour of fundamentals in the natural world is the way space and time mutually interact and the scriptural testimony about the essence of the resurrected Christ relating to time and space as found in 1 John 1:2. In this article, the author intends to investigate if this likeness could assist astrotheology in fulfilling its prophetical purpose, by clarifying the allencompassing cosmic agency of the triune God en route to the eschaton and steering clear of a pantheistic narrative. The author argues that astrotheology is well equipped to be a prophetic wormhole that relates space-time to eschatological transformation. We live in an entangled cosmos in which a relational Christ dwells, purposely at work towards transforming the universe. In this article, the author intends to explore these attributes further as well as the embedded nature of the incarnation and its cosmic fruits.